Working Memory and Consciousness: The Current State of Play - Persuh, Marjan; LaRock, Eric; Berger, Jacob (Frontiers in Human Neuroscience, 2018)
Working memory, an important posit in cognitive science, allows one to temporarily store and manipulate information in the service of ongoing tasks. Working memory has been traditionally classified as an explicit memory system – that is, as operating on and maintaining only consciously perceived information. Recently, however, several studies have questioned this assumption, purporting to provide evidence for unconscious working memory. In this paper, we focus on visual working memory and critically examine these studies as well as studies of unconscious perception that seem to provide indirect evidence for unconscious working memory. Our analysis indicates that current evidence does not support an unconscious working memory store, though we offer independent reasons to think that working memory may operate on unconsciously perceived information.